How Corporate Governance Influences Earnings Management: Evidence from Indonesian - Rifqi Andika Ramadhan (Advanced Business Journal, 2026)
Effective corporate governance serves as a fundamental pillar for maintaining transparency and accountability within financial disclosures, especially regarding the mitigation of opportunistic earnings management. Such practices, which involve the deliberate adjustment of financial reports to project a specific corporate image, fundamentally compromise the integrity of accounting data. Within the Indonesian context, where governance frameworks remain in a state of active development, investigating the link between oversight mechanisms and reporting behavior is essential for enhancing overall information quality. Current research evaluates how specific governance attributes influence the prevalence of manipulative reporting among firms listed on the Indonesia Stock Exchange (IDX), offering a clearer perspective on how structural oversight discourages financial distortion. Quantitative methodology guided the investigation, drawing upon longitudinal data from 150 publicly traded entities over a five-year window spanning 2017 to 2021. Multiple regression techniques facilitated the analysis of core governance indicators—such as the autonomy of the board and the proficiency of the audit committee—against levels of discretionary accruals. Empirical results demonstrate that heightened governance standards, particularly regarding independent directors and rigorous audit committee functions, lead to a measurable decline in earnings management activities. Organizations characterized by superior governance metrics exhibited significantly lower discretionary accruals, suggesting a higher commitment to transparent financial communication. Ultimately, this investigation underscores the critical necessity of implementing robust institutional controls to restrain financial manipulation and protect stakeholder interests. Strengthening these internal mechanisms remains vital for restoring investor confidence and ensuring that Indonesian capital markets remain competitive and trustworthy on a global scale.